"Duodenal Submucosal Glandular Lesion with Brunner and Paneth Cell Differentiation": A Variant of Pyloric Gland Adenoma? Morphologic and Immunohistochemical Similarities and Differences. (28th October 2020) - Alawad, M; Ilyas, G; Xia, R; Xie, Q; Shin, C
Abstract: Introduction/Objective: Duodenal epithelial polyps are reported in up to 3% of patients referred for upper endoscopy. Most include non-neoplastic lesions such as Brunner gland nodule/polyp and pancreatic or gastric heterotopia. Neoplastic lesions such as pyloric gland adenomas (PGA) are less frequently encountered and have the propensity to progress to adenocarcinoma. Herein we report a duodenal submucosal glandular lesion that has a morphologic resemblance to PGA, but very different in several aspects. We compare and contrast the characteristics of these two lesions. Methods: This was a 63-year-old man referred for an upper GI endoscopy for complaints of indigestion, dyspepsia, and weight fluctuation. Endoscopy showed a 13 mm polypoid lesion in the second portion of the duodenum, opposite to and separate from the ampulla. An en-bloc hot snare was used to resect the polyp. Histopathologic examination showed features reminiscent of PGA, namely a complex submucosal proliferation of tightly packed variably dilated glands and villous fronds lined by a monolayer of columnar cells with basally located round nuclei and prominent nucleoli. In contrast, however, the columnar cells in most of the lesion contained abundant mucinous cytoplasm resembling Brunner's glands as well as areas of prominent paneth cell differentiation. The characteristic amphophilic ground glass cytoplasm of PGAs was only noted in a minor component of the lesion. MUC6 and MUC5AC, immunostains that are typically expressed in PGA, were negative. Additionally, p53 showed a wild-type pattern, beta- catenin showed normal membranous staining, and the Ki-67 index was low. Results: After review of the literature and expert consultation, we were not able to fully classify this lesion under any documented entity, however, we believe that it could be akin to PGA. Authors hypothesized that PGAs may originate from stem cells within Brunner glands as a response to chronic injury. These cells may then differentiate upwards, forming gastric foveolar metaplasia or downwards giving rise to Brunner gland hyperplasia. Conclusion: Based on this hypothesis, the proliferating cells are prone to mutations resulting in a hyperplasia/metaplasia to dysplasia sequence that leads to the formation of PGAs or lesions such as the one demonstrated here.